B96: a complete core–shell structure with high symmetry. Issue 26 (6th June 2022) - Sai, Linwei; Wu, Xue; Li, Fengyu
Abstract : A complete core–shell B96 is highly symmetric ( T h ) and stable, and exhibits a superatomic electronic configuration and spherical aromaticity. Abstract : A complete core–shell and highly symmetric B96 was designed. The core–shell B96 of T h symmetry is energetically favorable compared to the bilayer motif and the core–shell structure can be well maintained during first-principles molecular dynamics simulations at high temperatures (up to 1000 K). Moreover, it exhibits a superatomic electronic configuration and spherical aromaticity. Our theoretical work not only confirmed that the core–shell structural pattern is more energetically favorable for large-sized boron clusters, but also provided a strategy to design large boron clusters with a core–shell structure of high symmetry.